Targeting Elastase for Molecular Imaging of Early Atherosclerotic Lesions. Issue 3 (March 2017) - Glinzer, Almut; Ma, Xiaopeng; Prakash, Jaya; Kimm, Melanie A.; Lohöfer, Fabian; Kosanke, Katja; Pelisek, Jaroslav; Thon, Moritz P.; Vorlova, Sandra; Heinze, Katrin G.; Eckstein, Hans-Henning; Gee, Michael W.; et al.
Abstract : Objective—: Neutrophils accumulate in early atherosclerotic lesions and promote lesion growth. In this study, we evaluated an elastase-specific near-infrared imaging agent for molecular imaging using hybrid fluorescence molecular tomography/x-ray computed tomography. Approach and Results—: Murine neutrophils were isolated from bone marrow and incubated with the neutrophil-targeted near-infrared imaging agent Neutrophil Elastase 680 FAST for proof of principle experiments, verifying that the elastase-targeted fluorescent agent is specifically cleaved and activated by neutrophil content after lysis or cell stimulation. For in vivo experiments, low-density lipoprotein receptor–deficient mice were placed on a Western-type diet and imaged after 4, 8, and 12 weeks by fluorescence molecular tomography/x-ray computed tomography. Although this agent remains silent on injection, it produces fluorescent signal after cleavage by neutrophil elastase. After hybrid fluorescence molecular tomography/x-ray computed tomography imaging, mice were euthanized for whole-body cryosectioning and histological analyses. The in vivo fluorescent signal in the area of the aortic arch was highest after 4 weeks of high-fat diet feeding and decreased at 8 and 12 weeks. Ex vivo whole-body cryoslicing confirmed the fluorescent signal to locate to the aortic arch and to originate from the atherosclerotic arterial wall. Histological analysis demonstrated the presence of neutrophils in atherosclerotic lesions. Conclusions—: This study provides evidence that elastase-targeted imaging can be used for in vivo detection of early atherosclerosis. This imaging approach may harbor potential in the clinical setting for earlier diagnosis and treatment of atherosclerosis. Abstract : Supplemental Digital Content is available in the text.